Tales of dracula ants: the evolutionary history of the ant subfamily Amblyoponinae (Hymenoptera: Formicidae). (July 2016) - WARD, PHILIP S.; FISHER, BRIAN L.
Abstract: The ants in the subfamily Amblyoponinae are an old, relictual group with an unusual suite of morphological and behavioural features. Adult workers pierce the integument of their larvae to imbibe haemolymph, earning them the vernacular name 'dracula ants'. We investigate the phylogeny of this group with a data set based on 54 ingroup taxa, 23 outgroups and 11 nuclear gene fragments (7.4 kb). We find that the genus Opamyrma has been misplaced in this subfamily: it is a member of the leptanilline clade and sister to all other extant Leptanillinae. Transfer of Opamyrma to Leptanillinae renders the Amblyoponinae monophyletic. The enigmatic Afrotropical genus Apomyrma is sister to all other amblyoponines, and the latter cleave into two distinct and well‐supported clades, here termed POA and XMMAS. The POA clade, containing Prionopelta, Onychomyrmex and Amblyopone, is well resolved internally, and its structure supports synonymy of the genus Concoctio under Prionopelta (syn.n. ). The XMMAS clade comprises two well‐supported groups: (i) a predominantly Neotropical clade, for which we resurrect the genus name Fulakora (stat.r., stat.n. ), with junior synonyms Paraprionopelta (syn.n. ) and Ericapelta (syn.n. ); and (ii) the remaining taxa, or 'core XMMAS', which are manifested in our study as a poorly resolved bush of about a dozen lineages, suggesting rapid radiation at the time of their origin. Most of these XMMAS lineages have been assigned to the catch‐all genus Stigmatomma, but the more distinctive elements have been treated as separate genera ( Xymmer, Mystrium, Myopopone and Adetomyrma ). Resolution of basal relationships in the core XMMAS clade and reconfiguration of ' Stigmatomma ' to restore monophyly of all named genera will require more extensive genetic data and additional morphological analysis. However, the genus Bannapone can be synonymized under Stigmatomma (syn.n. ) because it is embedded within a clade that contains S. denticulatum, the type species of Stigmatomma . Divergence dating analysis indicates that crown Amblyoponinae arose in the mid‐Cretaceous, about 107 Ma (95% highest probability density: 93–121 Ma). The POA and XMMAS clades have estimated crown ages of 47 and 73 Ma, respectively. The initial burst of diversification in the core XMMAS clade occurred in the Late Paleocene/Early Eocene (50–60 Ma). Ancestral range reconstruction suggests that amblyoponines originated in the Afrotropics, and dispersed to the Indo‐Malayan region and to the New World. During none of these dispersal events did the ants break out of their cryptobiotic lifestyle.